ORGANIZATIONAL COMMITMENT AND ITS RELATIONSHIP TO QUALITY OF WORK LIFE IN LOCAL ADMINISTRATION: A CASE STUDY OF GUELMA - Firdaws Hafiane; Zedira Khammar (International Journal of Innovative Technologies in Social Science, 2025)
Work engagement represents a fundamental element that management strives to achieve by meeting the needs of individuals, increasing their level of loyalty and helping them achieve their goals, which contributes to strengthening their desire to continue within the organization, as it is one of the most important indicators of the quality of life at work. This study aims to explore the nature of the relationship between job engagement and its different dimensions in the commune of Guelma, as an Algerian local government, and the quality of life at work. It also aims to identify the extent to which the municipality applies the standards of quality of life at work and to measure the level of engagement of its employees, in addition to studying how the quality of life at work contributes to strengthening the commitment of individuals to management. This aims to draw a clear picture of the reality of the quality of life at work and the level of job engagement in the commune of Guelma.